The Effect of COVID-19 on the Performance of Listed Firms: Do the governments’ policies and vaccination rates play a role? Evidence from countries in the Middle East and North Africa - El Bassioni, Mofida (AUC Knowledge Fountain, 2022)
This study uses a quantitative approach to estimate the empirical results of COVID-19, stringency index, and vaccination rates on the stock returns of Bahrain, Egypt, Morocco, Oman, Qatar, Saudi Arabia, Tunisia, and UAE. Additionally, the researcher included firm-specific variables such as liquidity and leverage, total capital, employees, and date of incorporation. Total capital and employees were used as proxies for company size and for whether the firm is capital intensive or not, while date of incorporation was used as a proxy for company age. Additionally, the researcher created interaction strings between COVID-19 cases and stringency index, COVID- 19 cases and vaccines, COVID-19 deaths and stringency index, and COVID-19 deaths and vaccines. To test whether these variables affect the stock returns, the researcher ran a Hausmann test to determine whether a fixed effect method or a random effect method is more appropriate to the panel data. The P-value was significant, and hence the researcher used a fixed-effect method. Moreover, the researcher used a Chow test to test whether a structural change existed pre-COVID versus during COVID-19, and the p-value was significant, and hence the researcher concluded the existence of a structural change. The results of the study indicate that COVID-19 cases and stringency index negatively affect the stock returns of listed firms in the MENA region. Moreover, vaccination rates positively affect stock returns by a higher magnitude than that of COVID-19 cases or stringency index. Firm-specific variables such as liquidity, leverage, total capital, total employees, and date of incorporation play a role in the returns of listed firms in the MENA region when the returns are regressed on the number of COVID-19 reported cases. Furthermore, COVID- 19 had a negative effect on stock returns of firms operating in the financial services, energy, power and utilities, tourism, healthcare and pharmaceuticals, chemicals, multi-utilities, logistics, construction and machinery, textiles, apparel and luxury goods, and insurance industries. Furthermore, government policies were able to countereffect the negative effect of COVID-19 deaths on stock returns for each of the 10 industries. The COVID-19 effect on the stock returns was greater than the government policies effect on stock returns for Morocco, Oman, Qatar, Saudi Arabia, and UAE at different significance levels. Vaccination rates have a positive effect on stock returns with a magnitude higher than the coefficients of COVID-19 cases or stringency index. The string variable between COVID-19 cases and vaccination rates is positive, implying that the positive effect of vaccination rates on the stock returns was able to countereffect the negative effect of COVID-19 cases on stock returns.